Cost-effectiveness of minimally invasive sacroiliac joint fusion [Corrigendum] - Cher DJ; Frasco MA; Arnold RJG; Polly DW (Dove Medical Press, 2016)
Cher DJ, Frasco MA, Arnold RJ, Polly DW. Clinicoecon Outcomes Res. 2016;8:1–14.Daniel J Cher is an SI-BONE employee. Renee JG Arnold and Melissa A Frasco are employees of Quorum Consulting, hired by SI-BONE to help prepare and evaluate the cost-utility model. David Polly is an investigator in clinical research studies sponsored by SI-BONE but has no financial interest in the company. The authors report no other conflicts of interest in this work.View original article by Cher et al.